Care for foreign body airway obstruction (OVACE) during infant food introduction - Santos, Rafael de Carvalho dos; Medeiros, Sarah Gomes; Rocha, Priscilla de França do Prado da; Coutinho, Ana Lúcia da Costa; Ramos, Thais de Souza; Ribeiro, Charlene da Silva (Seven Editora, 2024)
According to the guidelines of the agency that regulates health worldwide, it is recommended that breastfeeding be the only nutrition until the baby’s first six months and potentiating until the age of two years or infant acceptance, the introduction of additional foods is suggested concomitantly (Brazilian Society of Pediatrics, 2021). DOI:https://doi.org/10.56238/sevened2024.007-033